Dual Superlyophobic Aliphatic Polyketone Membranes for Highly Efficient Emulsified Oil–Water Separation: Performance and Mechanism - Cheng, Liang; Wang, Da-Ming; Shaikh, Abdul Rajjak; Fang, Li-Feng; Jeon, Sungil; Saeki, Daisuke; Zhang, Lei; Liu, Cui-Jing; Matsuyama, Hideto (ACS applied materials & interfaces, 2018)
Efficient treatment of difficult emulsified oil–water wastes is a global challenge. Membranes exhibiting unusual dual superlyophobicity (combined underwater superoleophobicity and underoil superhydrophobicity) are intriguing to realize high-efficiency separation of both oil-in-water and water-in-oil emulsions. For the first time, a robust polymeric membrane demonstrating dual superlyophobicity to common apolar oils was facilely fabricated via a simple one-step phase separation process using an aliphatic polyketone (PK) polymer, thanks to a conjunction of intermediate hydrophilicity and re-entrant fibril-like texture upon the prepared PK membrane. Further chemical modification to improve surface hydrophilicity slightly can enable dual superlyophobicity to both apolar and polar oils. It is found that a nonwetting composite state of oil against water or water against oil was obtainable on the membrane surfaces only when the probe liquids possess an equilibrium contact angle (θow or θwo) larger than the critical re-entrant angle of the textured surfaces (73°), which can explain the existences of dual superlyophobicity and also the nonwetting to fully wetting transitions. A simple design chart was developed to map out the operational windows of material hydrophilicity and re-entrant geometry, that is, a possible zone, to help in the rational design of similar interfacial systems from various materials. Switchable filtrations of oil-in-water and water-in-oil nanoemulsions were achieved readily with both high flux and high rejection. The simplicity and scalability of the membrane preparation process and the well-elucidated underlying mechanisms illuminate the great application potential of the PK-based superwetting membranes.